The Concept of the Grotesque in Literature: Friedrich Dürrenmatt’s Play The Physicists and Its Turkish Translation - Meltem Kılıç; Arsun Uras (Studien zur Deutschen Sprache und Literatur)
The grotesque is a form of humor in which contradictory concepts are intertwined and first emerged in the West. Although initially a genre used in the fine arts, it later played an important role in world literature and influenced non-Western literature. The main purposes of this study are to examine the Turkish translation of Die Physiker (The Physicists), a two-act play with grotesque elements written by the Swiss author and painter Friedrich Dürrenmatt, one of the most important representatives of this genre to be introduced to Türkiye through translation who glorified this concept in both his paintings and plays and successfully displayed all its features, and to discuss the reflection of the grotesque in the target language and culture. To this end, the study analyzes the translation decisions of translator Mustafa Tüzel in his 2005 translation and questions the function of this translation in the Turkish literary system. The concept of the grotesque and its characteristics are discussed alongside its place and importance in Dürrenmatt’s life through the play Die Physiker and its translation. The aims here are to show how the author’s character is as prone to the grotesque as his view of the world and to draw attention to the fact that his close relationship with this genre can be a great help in creating grotesque works. The study does not evaluate the work through the concept of performability due to the present edition of the examined work being intended for literary readers.